Kajian Minyak Serai Wangi (Cymbopogon nardus L.) terhadap Aedes aegypti - Yustin Nur Khoiriyah; Nurminha Nurminha (Jurnal Kesehatan, 2021)
The Aedes aegypti mosquito can develop an immune system against the insecticide used. Control efforts with the use of insecticides are no longer effective if the target insects have become resistant. So there needs to be an effort to overcome the insect resistance that is targeted. Citronella grass is an herbal plant that can be used as an ingredient in vegetable pesticides. The leaves and stems are distilled to produce essential oil known as citronella oil. This research is about studying the effects of citronella oil against the resistance of the vector carrier for dengue fever, namely Aedes aegypti. The detection of citronella essential oil (Cymbopogon nardus L.) by Thin Layer Chromatography showed a reduction in UV254 visualization (Rf 0,68). The resistance test showed that the mortality percentage of adult mosquitoes Aedes aegypti exposed to 0.03% alphacymethrin was 73,7% resistant criteria (<90%). The mortality percentage of adult mosquitoes Aedes aegypti exposed to Alphacypermethrin (0,03%) and citronella oil was 2,5% each; 5%; 7,5% and 10% with treatment time 15 respectively, namely 18,7%, 50,7%, 70,7% and 82,7%; the treatment time of 30 minutes consecutively is 62,7%, 89,3%, 96% and 97,3% and the treatment time is 60 minutes respectively, namely 93,3%, 98,7%, 98,7% and 100%. There was an increase in the percentage of mosquito deaths exposed to the combination of alphacypermethrin and citronella oil, compared to those without citronella oil, this indicates that mosquitoes are more susceptible and resistance has decreased due to exposure to citronella oil.